2011
DOI: 10.1002/jbm.a.33305
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced MC3T3 preosteoblast viability and adhesion on polyelectrolyte multilayer films composed of glycol‐modified chitosan and hyaluronic acid

Abstract: Layer-by-layer polyelectrolyte films made of the naturally derived polysaccharides chitosan (CHI) and hyaluronic acid (HA) constitute a well-studied system for the development of cell-responsive biointerfaces. However, many cell lines exhibit decreased adhesion to CHI/HA multilayer films, particularly as the number of bilayers is increased. Here, our group demonstrates that films composed of glycol-modified chitosan exhibit significantly improved MC3T3 preosteoblast adhesion and viability compared to correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…147,148 The Hammond Lab has made considerable progress with these materials for temporary protection and variable-timed release of therapeutic cargos via diffusion, stimuli-response, and/or network degradation. 149153 For instance, naturally derived LbL films were assembled through electrostatic complexation between anionic poly(β- l -malic acid) and cationic chitosan in aqueous conditions.…”
Section: Biotherapeutic Stabilization: Storage Release and Bioresismentioning
confidence: 99%
“…147,148 The Hammond Lab has made considerable progress with these materials for temporary protection and variable-timed release of therapeutic cargos via diffusion, stimuli-response, and/or network degradation. 149153 For instance, naturally derived LbL films were assembled through electrostatic complexation between anionic poly(β- l -malic acid) and cationic chitosan in aqueous conditions.…”
Section: Biotherapeutic Stabilization: Storage Release and Bioresismentioning
confidence: 99%
“…Holmes and Trabizian prepared alternate layers of Gly-C 43 and HA by deposition in their study of MC3T3 preosteoblast viability and adhesion on chitosan-HA films [47]. Films with five or more bilayers of Gly-C/HA displayed high cells adherence and viability attributed to surface topography, roughness, and chemistry characteristics that could be useful in drug and gene delivery and TE applications.…”
Section: Chitosan and Hamentioning
confidence: 99%
“…The hydrophilicity of the biomaterial is an important factor for cell adhesion, and thus improved surface hydrophilicity is beneficial to the interactions between biomaterials and cells. 19 For the m-MPC, the results showed that the water contact angle of the m-MPC decreased from 56° to 0° with the increase of m-MS from 0 w% to 40 w% in the composite, indicating that the m-MS content had significant effects on the hydrophilicity of the m-MPC. The remarkable improvement in hydrophilicity of the m-MPC through incorporation of m-MS into PCL-PEG-PCL suggests that the addition of inorganic bioactive material into polymer is a good way to enhance the hydrophilicity.…”
mentioning
confidence: 93%